Uncovering the history of recombination and population structure in western Canadian stripe rust populations through mating type alleles - Samuel Holden; Guus Bakkeren; John Hubensky; Ramandeep Bamrah; Mehrdad Abbasi; Dinah Qutob; Mei-Lan de Graaf; Sang Hu Kim; Hadley R. Kutcher; Brent D. McCallum; Harpinder S. Randhawa; Muhammad Iqbal; et al. (BMC Biology, 2023)
Abstract Background The population structure of crop pathogens such as Puccinia striiformis f. sp. tritici (Pst), the cause of wheat stripe rust, is of interest to researchers looking to understand these pathogens on a molecular level as well as those with an applied focus such as disease epidemiology. Cereal rusts can reproduce sexually or asexually, and the emergence of novel lineages has the potential to cause serious epidemics such as the one caused by the ‘Warrior’ lineage in Europe. In a global context, Pst lineages in Canada were not well-characterized and the origin of foreign incursions was not known. Additionally, while some Pst mating type genes have been identified in published genomes, there has been no rigorous assessment of mating type diversity and distribution across the species. Results We used a whole-genome/transcriptome sequencing approach for the Canadian Pst population to identify lineages in their global context and evidence tracing foreign incursions. More importantly: for the first time ever, we identified nine alleles of the homeodomain mating type locus in the worldwide Pst population and show that previously identified lineages exhibit a single pair of these alleles. Consistently with the literature, we find only two pheromone receptor mating type alleles. We show that the recent population shift from the ‘PstS1’ lineage to the ‘PstS1-related’ lineage is also associated with the introduction of a novel mating type allele (Pst-b3-HD) to the Canadian population. We also show evidence for high levels of mating type diversity in samples associated with the Himalayan center of diversity for Pst, including a single Canadian race previously identified as ‘PstPr’ (probable recombinant) which we identify as a foreign incursion, most closely related to isolates sampled from China circa 2015. Conclusions These data describe a recent shift in the population of Canadian Pst field isolates and characterize homeodomain-locus mating type alleles in the global Pst population which can now be utilized in testing several research questions and hypotheses around sexuality and hybridization in rust fungi.